2017
DOI: 10.1016/j.jff.2017.07.046
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo modeling of lipid bioaccessibility and digestion from almond muffins: The importance of the cell-wall barrier mechanism

Abstract: HighlightsWe investigated the mechanisms of lipid bioaccessibility from almond muffins.An in vitro dynamic gastric model was used to simulate human digestion.A pilot ileostomy study was performed to define the rate of lipid release.Microstructural analysis proved that some lipid remained encapsulated within matrix.The cell-wall is the main factor regulating the lipid bioaccessibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 27 publications
1
42
0
1
Order By: Relevance
“…Overall, the fatty acid bioaccessibility values found by the current study and previous 2,3,6,19 in vitro studies are in agreement with the results of a study using human subjects, where it was found that the absorption of fatty acids from almond particles between 1.7-3.4 mm in size was approximately 10%, 8 which is higher than the values predicted by the theoretical model for particles of this size (6.7% for 1.7 mm particles and 3.4% for 3.4 mm particles). This underprediction could have been due to the breakdown of almond particles during gastric digestion by human subjects.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Overall, the fatty acid bioaccessibility values found by the current study and previous 2,3,6,19 in vitro studies are in agreement with the results of a study using human subjects, where it was found that the absorption of fatty acids from almond particles between 1.7-3.4 mm in size was approximately 10%, 8 which is higher than the values predicted by the theoretical model for particles of this size (6.7% for 1.7 mm particles and 3.4% for 3.4 mm particles). This underprediction could have been due to the breakdown of almond particles during gastric digestion by human subjects.…”
Section: Discussionsupporting
confidence: 80%
“…9,10 Limited lipid bioaccessibility from almonds and other nuts has also been linked to improved metabolic markers in type 2 diabetes, 11 cardiovascular disease, 12,13 and obesity. 14 Previous studies have investigated the digestion of almonds using both in vitro 2,3,5,15 and in vivo [8][9][10][16][17][18][19] methods, and it has been observed that smaller particles led to higher lipid bioaccessibility than larger particles. 2,3,19 Additionally, researchers have reported size reduction of peanut particles during in vitro gastric digestion in a model that simulated the motility of the human stomach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The digestion rate of WB protein was possibly influenced by the concentration of pepsin, acidity, the temperature of the stomach, and the type of protein needed to be digested. Moreover, we observed in an orthogonal test that time factor has a significant effect on the fat digestion, similar study previously conducted by (Grassby et al ., ), who found the maximum lipid digestibility of 9 h in small muffins using in vitro dynamic gastric model.…”
Section: Resultsmentioning
confidence: 99%
“…Because WB plant cell wall contains a higher proportion of cellulose, it is assumed that starch, protein, fat content still remained in WB particles, but as compared to raw WB, enzymatic digestion processes were successful enough to remove starch, protein, and fat from fibre structure. The two possible mechanisms responsible for these effects can be a reduction of particle size (Grassby et al ., ) and in vitro digestion conditions (Hollebeeck et al ., ). One key finding of this study was the differences in intrinsic susceptibility of the raw WB to α‐amylase, pepsin, and pancreatin enzymes, hydrolysis became less pronounced when the macronutrients were encapsulated within plant cells, i.e.…”
Section: Resultsmentioning
confidence: 99%